UNDERSTANDING THE CONCEPT OF DEWATA SÉUWA’E IN THE TAFSIR AL-MUNIR: AN ANALYTICAL STUDY OF BUGIS TAFSIR - Fitra, Annisa (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2025)
This research explores the understanding of the concept of Dewata Séuwa’e in Tafsir al-Munir, which is one of the important aspects of Bugis religious belief. Using the approach of tafsir studies and cultural context, this research aims to explain the meaning and significance of the term, as well as identify how the understanding of the term Dewata Séuwa’e is reflected in Daud Ismail's interpretation of his tafsir. This research uses the theory of vernacularization popularized by Anthony H. Johns by understanding the linguistic elements and cultural praxis contained in Tafsir al-Munir, especially the verses that contain the term Dewata Séuwa’e,as well as a contextual approach to understand how the concept relates to the cultural context of Bugis society. Through an in-depth analysis of Daud Ismail's interpretation, this study seeks to gain a comprehensive understanding of how the term Dewata Séuwa’e is interpreted in Tafsir al-Munir and the religious context of Bugis society before and after the advent of Islam. The results of this study are expected to contribute to further understanding of Bugis religious heritage, especially in the scientific field of Qu r'anic interpretation.